134 HRT is not detrimental to survival in women diagnosed with stage 1B–2B (FIGO 2009) adenocarcinomas of the cervix aged less than 50. (13th November 2020) - Richardson, A; Watson, L; Persic, M; Phillips, A
Abstract : Introduction: Studies purporting the safety of HRT in cervical cancer have predominantly included patients with squamous disease. Pathological studies have identified increasing estrogen receptor positivity in cervical adenocarcinomas. A recent small case-control study suggested a trend towards reduced survival following HRT use in adenocarcinomas. The objective of this study was to assess if HRT use in patients treated for cervical adenocarcinomas was detrimental to survival. Methods: A retrospective review of all women aged ≤50, with stage 1B-2B cervical adenocarcinoma diagnosed between 1/11/00–24/9/19. Women were categorized as: ovaries conserved (OVCON); or Iatrogenic menopause with (IM-HRT) or without (IM-NOHRT) HRT. HRT use was defined on an intention to treat basis. Statistical analysis was performed using Kaplan-Meier and Cox proportional hazards methods. Results: 58 women with mean age 38.6±6.5 yrs were included in the study. 25(43.1%) had OVCON, 12(20.7%) had IM-NOHRT and 21(36.2%) had IM-HRT. No menopause-associated deaths occurred. 5-year disease specific survival was 95% in OVCON, 95% in IM-HRT and 64% in IM-NOHRT (p = 0.041 and 0.016 between IM-NOHRT and IM-HRT and OVCON respectively). On multivariate analysis, adjusting for stage, grade, treatment approach and nodal status neither differences remained significant. 5-year progression free survival was 80% in OVCON, 91% in IM-HRT and 66% in IM-NOHRT but this was not statistically significant (p= 0.077). Conclusions: HRT or ovarian conservation does not appear to be detrimental to survival in cervical adenocarcinomas. In this small dataset, there is a trend towards improved survival with HRT. Larger studies are required to substantiate these findings.